Effect of Adding Thyme Powder on the Physiological Characteristics of Quail - Ameen, Gulala. W. (American Journal of Botany and Bioengineering, 2026)
The aim of the current research was to determine the impact of dietary supplementation by thyme (Thymus vulgaris) powder on the Japanese quail (Coturnix coturnix japonica) with respect to a few hematological and biochemical measurements. Sixty-four, 45 days old, birds collapsed randomly into four dietary treatments in a completely randomized design (CRD). The four replicas were used in each treatment and each replica was made up of four birds. The trial period was eight weeks (56 days). The diets were as follows: T1, a basic diet free of thyme (control); T2, a basic diet with 0.5 percent thyme powder in it; T3, a basic diet containing 0.75 percent thyme powder in it; and T4, a basic diet containing 1 percent thyme powder in it. Statistical analyses showed that thyme supplementation produced significant (P < 0.05) changes in hemoglobin, packed cell volume, white blood cell, and lymphocyte proportion with the largest response changes being recorded in 0.75 percent inclusion rate. Parameters of lipid-profile also showed a change; the total cholesterol showed a very significant decrease, and the level of the high-density lipoprotein (HDL) in the T3 group was higher than in the other treatment groups. There were no statistically significant differences between the groups in terms of total protein, albumin and globulin and uric acid concentrations. Hepatic enzyme levels, such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), were within the normal physiological range, which showed that liver functioning was not harmed. In general, the addition of thyme powder at a 0.75 percent inclusion level to the diet improved the hematological as well as the specific biochemical parameters without damaging the hepatic integrity. Therefore, thyme powder can be considered to have an effective natural feed additive with physiological and immunological effects to Japanese quail.